The Use of Animation Media Based on Character Education to Improve Students’ Writing Narrative Ability - Ningsih, Tri Siska; Sutiyono, Akhmad; Rohana, Rohana; Wiratno, Purna (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
The purpose of the study was to determine and describe the effectiveness of character education-based animation media in improving the ability to compose narratives for fifth graders at SD Negeri 3 Waringinsari Barat for the 2020/2021 academic year. The underlying problem is that animation media has never been used in learning to compose narratives. The research method uses classroom action research. The subjects of this study were 28th-grade students of SD Negeri 3 Waringinsari Barat, Sukoharjo District, Pringsewu Regency. The data were collected using observations, questionnaires, interviews, and narrative writing tests. The research procedure uses four stages, namely planning, implementation, observation, and reflection, and is carried out in 2 research cycles. Data analysis was carried out by quantitative descriptive analysis using the percentage formula. The results of the study indicate that the use of animation media can increase the effectiveness of the learning process on the ability to compose narratives for fifth-grade students of SD Negeri 3 Waringinsari Barat. The improvement can be seen in the change from pre-action, cycle I to cycle II. The results of the student's ability to compose narratives in the first cycle obtained an average score of 62 which increased to 72 in the first cycle and increased to 82 in the second cycle.